Antroponímia de Toledo-Paraná-1954-2004:aspectos inovadores - Grespan, Taiana (2014)
This work presents some results from survey of large scope and is part of project whose title is Anthroponymy, culture and identity in Marechal Cândido Rondon, Toledo and Missal (Project No. 35370/2011, registered in PRPPG, Unioeste). Through the analysis of 600 names (recorded between the years of 1954 and 2004), sought to understand the way in which the inhabitants of Toledo name their children and tried to investigate innovative phenomena in the nominator practices of Toledanos. The research is based on the assumptions of Anthroponomastic, subject from Linguistics responsible for studying the proper names of people. However, unlike most works in the area, which tend to an etymological methodology, in this research, sought to describe innovative features of standard anthroponomical of Toledo, with the etymology, for now, a minor role in our research. To this, we used the structuralist language bias, since we consider the name as a linguistic sign, endowed with significant and meaning, and Coseriu studies about the standard, intermediate level of linguistic description located between language and speech. As a result, it was observed that the community of Toledo introduces some innovative behaviors regarding the appointment of children, among them the choice of a double name or a modifier (like y, ll, nn, th, ph, etc.). Such phenomena were considered innovative because they did not present so often in the initial years of colonization from municipality and, in the final years of our corpus, there was a sudden increase in frequency.